Impact of Victim Offender Dialogue on Victims of Serious Crimes: A Longitudinal Cohort-Control Study, Colorado, 2017-2019 - Sliva, Shannon M. ([Verlag nicht ermittelbar], 2023)
The goal of this National Institute of Justice-funded research study was to determine the impact of High-Risk Victim Offender Dialogue (HR-VOD) on victims of serious or violent crimes and criminal offenders currently or previously under the supervision of a Colorado correctional facility or community supervision agency. Specifically, the research team conducted a longitudinal, mixed-methods cohort-control study, comparing the wellbeing of victims and offenders who participated in a facilitated restorative justice dialogue to the wellbeing of those who did not participate. Wellbeing of crime victims were measured by validated psychometric scales capturing trauma indicators, PTSD, depression, substance abuse behaviors, and physical and emotional health. In addition, qualitative interviews with participants built a multi-faceted contextual understanding of the impact of HR-VOD on victim trauma and healing and offender development. Interviews took place at enrollment in the VOD program, within 72 hours of the VOD intervention, and six months following the VOD intervention. This study was designed to inform practice and policy decisions about the use of HR-VOD in criminal justice settings in Colorado and nationally to improve criminal justice outcomes and ameliorate the effects of crime.